CONTROLLING IN ROLLING PRODUCTION OF ОАО «BMZ» - V. M. Machulin; V. E. Sidorchuk; S. N. Astratov (Литьë и металлургия)
Controlling is philosophy and way of thinking of leaders, oriented to effective development of the enterprise and economic usage of resources.